Pengaruh Store Atmosphere dan Emosi Positif Konsumen Terhadap Pembelian Impulsif (Studi Kasus Pada Konsumen Giant Hypermarket Pekanbaru) - khairani, zulia (Komunitas Manajemen Kompetitif, 2016)
This study aims to analize how much store atmosphere and consumers positive emotions influence to impulse buying on consumer in Giant Hypermarket Pekanbaru.The sample in this study was 100 consumers who shopped at Giant Hypermarket in last 3 months, with the method of sampling incidental and then do an analysis of the data obtained using the analysis of quantitative data include : validity and reliability, the classic assumption test, multiple regression analysis, hypothesis testing via t test, hypothesis testing via F test, and analysis of the coefficient of determination (R2). The study found that the store atmosphere partially has possitive effect but don’t significant to impulse buying, Positif emotion of consumers partially has possitive effect and significant on to Store Atmosphere. Store atmosphere andpositif emotion of consumers simultanly have positif effect and significant on impulse buying. Keywords: Consumer Behavior, Impulse Buying, Store Atmosphere, Possitive Emotion Of Consumer